Intrinsic gain and gain degradation modulated by excitation pulse width in a semiconducting conjugated polymer. (1st September 2017) - Lampert, Zach E.; Papanikolas, John M.; Lappi, Simon E.; Reynolds, C. Lewis
Highlights: Chemical stability of encapsulated MEH-PPV gain medium dependent on duration of pump laser pulses. Transient pulses (pulse width < PL lifetime): high stability, intrinsic gain measured. Quasi steady state pulses (pulse width > PL lifetime): low stability, 5× degraded gain measured. Quasi-steady-state pulses introduce thermal/photochemical defects that quench emission & degrade gain. Pump pulse width should be considered when optimizing optically pumped polymer lasers. Abstract: We have previously reported that substantially higher optical gain values can be achieved in the conjugated polymer poly[2-methoxy-5-(2′-ethylhexyloxy)-p-phenylene vinylene] (MEH-PPV) through use of transient excitation conditions. In the present paper, we report on a systematic investigation of this behavior to elucidate the physical mechanisms involved, which enables us to distinguish between the fundamental intrinsic gain and an excitation induced degraded gain. Using pump laser pulses having temporal widths longer and shorter than the photoluminescence (PL) decay time of MEH-PPV, both quasi-steady-state (QSS) and transient excitation regimes are explored in our encapsulated waveguide heterostructures [Si(1 0 0)/SiO2 /MEH-PPV/poly(methyl methacrylate)]. Under transient excitation (25 ps pump pulses), extremely large optical gain is observed, reaching a value of 700 cm −1 at a maximum pump energy density of 85 µJ/cm 2 . However, under QSS conditions (8 ns pulses), considerably lower gain coefficients are achieved with a maximum of ∼130 cm −1 at an energy density of 2, 000 µJ/cm 2 ; this factor of 5 decrease in optical gain performance is observed at the same excitation density as that for transient excitation using ps pulses. We have also employed unencapsulated waveguide structures [Si(1 0 0)/SiO2 /MEH-PPV/air], which allows us to achieve additional insight on gain degradation under QSS conditions. It is clear that the gain measured under transient conditions is more representative of the intrinsic gain whereas that determined in the QSS regime is degraded by defect-mediated dissociation of emissive states due to localized thermal and oxidative damage to the films. It is in the QSS regime in which most optical gain measurements to date have been performed. These results suggest that further optimization of MEH-PPV – and most likely other conjugated polymers – as a robust optical gain medium can be achieved by consideration of the excitation pulse width.